A thermal non-equilibrium model for predicting LNG boil-off in storage tanks incorporating the natural convection effect. (15th October 2021) - Duan, Zhongdi; Xue, Hongxiang; Gong, Xueru; Tang, Wenyong
Abstract: LNG boil-off in storage tanks is of particular significance to tank design, boil-off gas (BOG) management and thermoeconomic assessment. This paper aims to present a thermal non-equilibrium model to predict LNG boil-off performance, with incorporating all the major dynamics of liquid- and vapor-phases and their interactions. Integral-form equations of the buoyancy-driven flow are deduced to describe liquid natural convection and its effect on LNG boil-off. The thermodynamic response of the boil-off gas is modeled based on conservation laws of mass, energy and species, capable to predict the boil-off rate as well as the vapor superheating, pressure build up and composition variations. The model predictions show good correlations of the thermal response and temperature profiles with the experimental data, and the effectiveness to calculate natural convection. The results of the work indicate that the vapor superheating gives rise to additional boil-off loss in the initial boil-off period, and the liquid natural convection will strengthen LNG evaporation during long-term storage while remains little temperature rise that less than 1 °C. The thermal non-equilibrium effects can be effectively suppressed by a higher storage pressure and liquid filling, providing insight relevant to reducing the BOG rate and total boil-off loss. Highlights: A new thermal non-equilibrium model to predict LNG boil-off is developed. LNG natural convection is modeled instead of regarding the liquid as a lumped zone. Vapor superheating results in additional BOG loss at the initial boil-off period. Natural convection has a pronounced effect on LNG heat delivery and evaporation. Storage conditions towards reducing the boil-off loss on FLNG are analyzed.